Pelatihan Pembuatan Eco- Friendly Packaging Kuliner untuk Meningkatkan Pemasaran LPP-PEKKA Yayasan Masjid Agung Palembang - Suhel; Gustriani; Rika Henda Safitri; Melliny, Vinny Dwi (Outline Journal of Community Development, 2025)
This study explores the implementation of training programs aimed at enhancing the marketing of environmentally sustainable culinary products through eco-friendly packaging design and label creation. Concurrently, the label creation training focused on the design of informative and visually appealing labels that align with environmental sustainability principles, thereby enhancing the marketability and branding of culinary products. Evaluation results indicated a high level of effectiveness, with 93.93% of participants demonstrating a comprehensive understanding of the training content. Moreover, the technical training on label creation received a participant satisfaction rating of 93.09%, highlighting the program’s success in delivering both theoretical and practical knowledge. These findings underscore the significance of training programs in fostering innovation and sustainability within the culinary industry.